2016
DOI: 10.1186/s12888-016-0871-0
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorders and Axis I comorbidity in adolescent outpatients with ADHD

Abstract: BackgroundAttention deficit hyperactivity disorder (ADHD) is a lifelong condition which carries great cost to society and has an extensive comorbidity. It has been assumed that ADHD is 2 to 5 times more frequent in boys than in girls. Several studies have suggested developmental trajectories that link ADHD and certain personality disorders. The present study investigated the prevalence of ADHD, common Axis I disorders, and their gender differences in a sample of adolescent outpatients. We also wanted to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 68 publications
1
12
0
1
Order By: Relevance
“…The male: female ratio was 3:1, similar to that in other studies [ 24 ]. Irrespective of the total annual cost, average cost, and average number of visits, boys used the rehabilitation resources more than girls ( p < 0.05).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The male: female ratio was 3:1, similar to that in other studies [ 24 ]. Irrespective of the total annual cost, average cost, and average number of visits, boys used the rehabilitation resources more than girls ( p < 0.05).…”
Section: Discussionsupporting
confidence: 90%
“…ADHD has the potential to be a lifelong problem, particularly if untreated, and the burden of social costs and excessive care expenditure is significant [ 24 ]. However, in many countries, ADHD has not been diagnosed or has remained untreated, resulting in an increase in ineffective treatment and the costs incurred by this disease [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the generalizability of these results is limited to individuals seeking treatment for AUD. We also did not assess conduct disorder (CD), antisocial personality disorder (ASPD), or nicotine dependence symptoms that are often comorbid with ADHD (Korsgaard, Torgersen, Wentzel-Larsen, & Ulberg, 2016). These results may be reduced if CD, ASPD, or nicotine dependence symptoms are tested within the same model.…”
Section: Discussionmentioning
confidence: 99%
“…However, very most studies conducted in adolescents on this topic reported lower rates of cooccurrence of ADHD and BPD, compared to our findings. Korsgaard et al investigated personality disorders in adolescents and found that only 4 out of 21 ADHD patients (19%) also received a BPD diagnosis [34]. Similarly, Speranza et al reported that only 11% of subjects with BPD received an ADHD diagnosis as well in their clinical sample [23] compared to 33% in our sample.…”
Section: Discussionmentioning
confidence: 41%